2018
DOI: 10.4314/njt.v36i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of eco-friendly cellulosic nanoparticles potential as reinforcement agent in the production of natural rubber composites

Abstract: This research focuses on the use of cellulosic nanoparticles obtained from coconut husk, bamboo and cotton linter as reinforcing phase in natural rubber composites with the objective to study the effect of these cellulosic particles and loading ratio on the mechanical, thermal and morphological properties of the resultant composites. Vulcanized natural rubber composites were prepared using cellulosic nanoparticles obtained from bamboo (BNC), coconut husk (CHNC), cotton linter (CLNC) and carbon black (CB) as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Because of the hybrid network formed, which limits the movement of the PVA and soybean protein segments, complete decomposition of the soy fibres required another degradation step at ≈276 °C. It has been shown that proteins processed in the form of fibres to display an interconnected structure formed at the nanoscale that hinders degradation to higher temperatures (≈300 °C) [67,68]. Shifting of this peak to higher temperatures by chitosan treatment (291.4 °C) confirms this polymer ability to increase the thermal stability of the fabric.…”
Section: Resultsmentioning
confidence: 93%
“…Because of the hybrid network formed, which limits the movement of the PVA and soybean protein segments, complete decomposition of the soy fibres required another degradation step at ≈276 °C. It has been shown that proteins processed in the form of fibres to display an interconnected structure formed at the nanoscale that hinders degradation to higher temperatures (≈300 °C) [67,68]. Shifting of this peak to higher temperatures by chitosan treatment (291.4 °C) confirms this polymer ability to increase the thermal stability of the fabric.…”
Section: Resultsmentioning
confidence: 93%
“…A thermogravimetric analyzer (TGA, PerkinElmer, UK) was employed to investigate the thermal degradation behaviour of DCP ( Oboh et al., 2018 ). In detail, 10 mg of CP sample was placed into the crucible of the thermogravimetric analyzer and performed at temperatures of 30–900 °C and heating rates of 10, 20 and 30 °C/min under a nitrogen flow rate of 50 mL/min as a non-reacting inert gas.…”
Section: Methodsmentioning
confidence: 99%
“…14 Oboh et al used CNC, prepared via top to down method, in NR matrix to enhance the tensile strength. 15 However, the dispersion of cellulose in a hydrophobic polymer matrix like NR remains a matter of concern owing to its hydrophilic nature that arises from the presence of polar hydroxyl groups at the cellulose surface. A very low dispersion of CNC upon high time consumption has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Abraham et al reported incorporation of nano cellulose fibers into the NR latex via solution casting method 14 . Oboh et al used CNC, prepared via top to down method, in NR matrix to enhance the tensile strength 15 . However, the dispersion of cellulose in a hydrophobic polymer matrix like NR remains a matter of concern owing to its hydrophilic nature that arises from the presence of polar hydroxyl groups at the cellulose surface.…”
Section: Introductionmentioning
confidence: 99%